1964
DOI: 10.1210/jcem-24-1-35
|View full text |Cite
|
Sign up to set email alerts
|

The Natriuretic and Aldosterone-Suppressive Action of Heparin and Some Related Polysulfated Polysaccharides1

Abstract: In order to extend earlier observations on the natriuretic effect of heparinoids in man, the effect of several sulfated polysaccharides on urinary sodium and potassium excretion was studied in dogs receiving low sodium diets. In patients, the effect of heparinoids, not tested before, on the excretion of sodium, potassium, creatinine and aldosterone was studied to extend previous observations in man. The pattern of sodium excretion observed in dogs during treatment with certain heparinoids differs from that see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1966
1966
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…One additional factor which must be considered is the effect of heparin administration during each of the dialyses. Heparin in doses of 300-400 mg per day has been shown to suppress aldosterone excretion and promote natriuresis and potassium retention (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…One additional factor which must be considered is the effect of heparin administration during each of the dialyses. Heparin in doses of 300-400 mg per day has been shown to suppress aldosterone excretion and promote natriuresis and potassium retention (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…This decrease in total body potassium, which is frequently not reflected in its circulating levels, may include decrements in adrenal cortical potassium content, thereby suppressing aldosterone secretion. 3) The repeated heparin administration required for anticoagulation during dialysis might interfere with aldosterone secretion, since this agent is known to possess significant aldosterone inhibitory potential (114).…”
Section: Disparity Between Bioactivity and Immunoreactivitymentioning
confidence: 99%
“…Furthermore, heparin administration has resulted in clearing of edema fluid in congestive cardiac failure or the nephrotic syndrome (2, 3, 21). Schlatmann et al (2) and others (3) showed that the natriuretic and diuretic effects of heparin in congestive heart failure are associated with suppression of aldosterone secretion. There is, therefore, considerable evidence to indicate that heparin can reduce aldosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…(J Clin Endocr 27: 699,1967) H EPARIN is known to inhibit certain enzymes (1). In addition, administration of heparin or of related substances has been shown to reduce aldosterone secretion (2,3). This effect has been thought to result from heparin binding of angiotensin (4), or from heparin interference with renin activity (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation